Opportunities on the planting of medicinal and herbal plants in Malaysia - Mohd Ilham Adenan (Forest Research Institute of Malaysia (FRIM), Kepong, 52109 Kuala Lumpur (Malaysia). Medicinal Plants Division) (2013)
Raw materials of most medicinal and aromatic plants have been traditionally sourced from the natural forests. Continuous extraction from this source without concerted efforts to replace through replanting has inevitably led to the depletion of these important raw materials. With the growing interests in medicinal plants as new pharmaceutical products, there is a great need for sustainable supply of quality raw materials. The planting of medicinal and herbal plants, therefore, present an opportunity for economic gains.